Green bonds as a source of financing pro-environmental actions in Poland - Hajdys, Dagmara (Journal of Finance and Financial Law, 2020)
Climate changes and progressing environmental pollution enforce undertaking various actions of the global range. Implementation and execution of pro-environmental programs require appropriate financing. In 2007 a new instrument, referred to as green bonds, appeared in the market. Since that, a systematic and dynamic development of this segment of capital market has been observed. The development takes place in terms of values, a number of instruments and a number of issuers. In 2016 a pioneering issuance of green bonds issued by the Polish government appeared in the market. The objective of the study is to characterize green bonds issued by the Polish government to finance pro-environmental actions against the background of the global green market of debt securities. The hypothesis accepted in the study stated that the development of green bonds in Poland is determined by the development of the global green market of debt securities and is a response to a need for intensification of expenditure on pro-environmental programs.